The Position of the Guardian in Marriage Perspective of the Hanafi and the al-Shafi'i Madhhab - Rosmita; Afifah, Andi Nur; Nasaruddin (Universitas Islam Negeri Alauddin Makassar, 2022)
This article aims to determine and understand the position of the guardian in marriage according to the Hanafi and the al-Shafi’i madhhab, and its application to Islamic law (fiqh), as well as its actualization in social life. Furthermore, to obtain data and answers to these problems, descriptive qualitative (non-statistical) research was used, which focused on the normative approach method. The results found a difference between the Hanafi and the al-Shafi’i madhhab in viewing the position of a guardian in a marriage. The Hanafi madhhab views that a guardian in marriage is not a pillar but only a sunnah, hence, the absence of the guardian does not affect the ijab-qabūl. This is in contrast with the al-Shafi’i madhhab perspective, which places the guardian as one of the pillars, and the absence makes the consent of the qabūl invalid. There is also a sense of security that arises as a result of the guardian's permission. Therefore, because marriage is a life decision, women's choices need to be based on the instruction and knowledge of the guardian.